2009
DOI: 10.1029/2008wr007134
|View full text |Cite
|
Sign up to set email alerts
|

One‐dimensional numerical modeling of sediment transport and bed deformation in open channels

Abstract: [1] A one-dimensional numerical model for simulating unsteady flow and sediment transport in open channels is presented and tested. The flow hydrodynamics is represented by the shallow water equations, and the bed morphodynamics is represented by the Exner equation and an additional equation describing the nonequilibrium sediment transport. Sediment size distribution is represented by the median grain diameter and the standard deviation, instead of the usual modeling with multiple particle size classes. Variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 61 publications
0
67
1
2
Order By: Relevance
“…1D morphodynamic models are conceptually inferior to 2D or 3D models which can resolve local spatial differences in fl ow strength, but higher-dimension models based on the St-Venant or Navier-Stokes fl ow equations are still computationally too expensive for long-term morphological predictions over extended reaches (Kleinhans et al, 2008;El kadi Abderrezzak and Paquier, 2009). Rule-based 2D cellular models, which are computationally far more effi cient, can generate plausible generic behaviour (Murray and Paola, 1994) and have been used to simulate the long-term (Holocene) behaviour of specifi c river systems (Coulthard et al, 1999;, but they have not yet been shown to yield quantitatively accurate predictions of sediment transport and channel change in specifi c situations.…”
Section: Morphodynamic Modelmentioning
confidence: 99%
“…1D morphodynamic models are conceptually inferior to 2D or 3D models which can resolve local spatial differences in fl ow strength, but higher-dimension models based on the St-Venant or Navier-Stokes fl ow equations are still computationally too expensive for long-term morphological predictions over extended reaches (Kleinhans et al, 2008;El kadi Abderrezzak and Paquier, 2009). Rule-based 2D cellular models, which are computationally far more effi cient, can generate plausible generic behaviour (Murray and Paola, 1994) and have been used to simulate the long-term (Holocene) behaviour of specifi c river systems (Coulthard et al, 1999;, but they have not yet been shown to yield quantitatively accurate predictions of sediment transport and channel change in specifi c situations.…”
Section: Morphodynamic Modelmentioning
confidence: 99%
“…They have correctly predicted useful information such as an approximation of the total mass of sediments transported during a flood. Among other examples, [13] shows that with a one dimensional sediment transport model, they achieve reasonably good results in reproducing the bed changes due to a large flood event on the Ha!Ha! River (Canada).…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, numerical models can be used as a supplementary tool in analyzing the long-term processes. Attempts to investigate the sediment transport and morphological processes with numerical models have been made in a variety of studies of different time scales (for example, see Cao et al, 2002;Wu, 2004;El kadi Abderrezzak and Paquier, 2009;Chen et al, 2010;Zhang and Duan, 2011;among others). These models, sometimes called ''process-based" models because they solve coupled systems of hydrodynamic equations and sediment transport equations, successfully reproduced the fluvial processes in event-based simulations.…”
Section: Introductionmentioning
confidence: 99%